#TITLE_ALTERNATIVE# - (NIM 12206083); Pembimbing: Prof. Dr.-Ing. Ir.Rudi Rubiandini R. S., MARCEL
Casing Design for a directional well is different from vertical well, although principally both of them are same, calculating burst load, collapse load, tensile load, and bi-axial effect. The difference are in the directional well casing design, it also has to calculate the effect of bending load and drag load caused by the contact between casing string and borehole wall. The determination of the burst and collapse loads are a function of vertical deoth (TVD), while the determination of tension load, bi-axial effect, and drag loads are a function of casing length (MD). After finishing the calculations, it is concluded that the most increasing tension load and bi-axial effect took place at the curve section, then the vertical section, and the least is at tangent section. In the drag load calculation, it is obtained that the drag load is smaller than the tension load, thus the casing can be run until reach the target depth. With the existence of drag and the increasing angle on the casing, both will cause the tension load increase and the casing collapse resistance decrease. These will affect the way in designing the casing string, where a higher grade casing will be needed. After comparing the results between casing design calculation and casing string used in well X, it can be concluded that the casing string used is not efficient because it uses non-optimal casing grade. In calculation, there is still available lower-grade casing that do not violate the casing design parameter, thus making this lower-grade casing should be the one that used in the casing string design in well X.